The role of animal breeding with special regard to native pigs of food supply and rural development in Laos - Xayalath, Somsy; Balogh, Eszter; Rátky, József (Acta Agraria Debreceniensis, 2020)
The present paper explored the influence of breeding native pigs on livelihood conditions and the contribution of native pigs to the rural development and rural poverty reduction in the rural areas of Lao PDR. Pig production plays an important role in meat supply for both urban and rural areas of Laos. It is clear that most of the pig products in the country come from smallholder pig farms, and more than 90 percent of those products are the native pigs mostly raised by farmers in remote areas. In general, livestock production distributed between 15–18 percent to GDP, while most of animal production still remains as the traditional methods. Rural development is always the first priority of the Laos government since its independence in 1975, however, the poverty rate in rural areas remained high at 23% in 2018. It might block the development goal of the government which will lead the country out of the least development status by 2020. The food security and malnutrition in the rural or mountainous areas are considered as the majority issue that both government and several international organizations have been thriving hard to overcome, which researchers showed that more than 45% of children under 5 years of age were stunted, and 28% of them were underweight. Inspired of more than 50 % of the households in the rural areas of Laos reported they consumed chicken and pork at least one day a week. While native pigs play an important role on meat supply, it also constituted around 9–14 % of annual income of the households in rural areas. Therefore, the increase the production of pigs and poultry is one option to promote the meat supply to households in the rural areas of Laos. This paper will be a pathway to guide and identify for the final decision to what experiment will be implemented on Lao native pig in Laos (2021–2023) to complete the comparative study on reproductive physiology and reproductive management methods of Hungarian and Lao Indigenous pig breed. Which found it still needs further afford to research and improve more about native pig performance for all areas of productive and quality management.